Rancang Bangun Robot Pengangkut Sampah Pintar Menggunakan Mikrokontroler - Clara Robert Pangestu (JITCE (Journal of Information Technology and Computer Engineering), 2019)
Humans are living things that like all things that are clean and beautiful to look at, including environment around them. Nowadays, there are many people that conscious and care about environmental hygiene, but there are many of them that do the otherwise. Managing trash can in their residential area is one form of human awareness of environmental sanitation. Human's responsibility in keeping their health and the environment is not only to dispose of trash in its place but also to manage a fully loaded trash can. Because of the waste management problem, the writer made a smart garbage transport robot, which is a fully loaded trash can or a trash can that has methane in it can move automatically from a residential area to its landfill. Components that used to detect the condition of a trash can are Ultrasonic sensor that used to identifies a fully loaded trash can; MQ-4, a methane gas sensor to detect methane gas's level in the trash can; and photodiode sensor for the automatic trash can robot's line tracking to the landfill. The success rate of garbage transport robot is 4 out of 4 trials.